Answer: she made a mistake between 1 and 2
Answer:
Acute, equilateral
Step-by-step explanation:
![\bf \stackrel{eg}{5x+8}-\stackrel{fg}{3x}=\stackrel{ef}{6x-4}\implies2x+8=6x-4\implies 12=4x \\\\\\ \cfrac{12}{4}=x\implies 3=x\qquad \qquad \stackrel{ef}{6(3)-4}](https://tex.z-dn.net/?f=%5Cbf%20%5Cstackrel%7Beg%7D%7B5x%2B8%7D-%5Cstackrel%7Bfg%7D%7B3x%7D%3D%5Cstackrel%7Bef%7D%7B6x-4%7D%5Cimplies2x%2B8%3D6x-4%5Cimplies%2012%3D4x%0A%5C%5C%5C%5C%5C%5C%0A%5Ccfrac%7B12%7D%7B4%7D%3Dx%5Cimplies%203%3Dx%5Cqquad%20%5Cqquad%20%5Cstackrel%7Bef%7D%7B6%283%29-4%7D)
and surely you know how much that is.
55
Step-by-step explanation:
Answer:
glad my answer helped you.
Step-by-step explanation:
hope that because i showed the steps, it will help you if you come across a problem like that in the future too!